Komparasi Perlindungan Data Pribadi di Indonesia dan Uni Eropa - Syafira Agata Ramadhani (Jurnal Hukum Lex Generalis, 2022)
The construction of regulations related to privacy protection has actually been known for a long time in Indonesia. Nomenclature about privacy can at least be found by the Criminal Code which contains several articles of criminal acts related to privacy such as prohibition to open papers and prohibition of entering land / private property. Define privacy as a right that is inherent and protected by the Constitution in Indonesia. So the urgency of personal data protection is a very vital thing to note. This is not only Indonesia's position as a state of law, but also the perception of personal data protection related to the concept of privacy, which the concept of privacy itself is the idea of maintaining personal integrity and dignity, because the right to privacy includes the right to determine, provide or not to provide personal data. This can not be separated from the cultivation of economic value to a data, so personal data is often also said as an asset or commodity. Personal data is data that is economically valuable because in the age of digitalization in the concept of the Industrial Revolution 4.0, data is a more valuable mine than gold or oil. But the problem is, is the personal data protection arrangement in Indonesia mature? In this article, the author will compare with the European Union.